SOEP-IS 2016 - BIOAGE: Variables from the modules of questions on children - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The bioage data file is generated using information collected in the "Mother & Child" and "Parent" questionnaires. It contains information on every child, on which at least one questionnaire has been answered by one of the parents. Each row can be identified by the ID of the child (pid), the survey year (syear) and the ID of the respondent (pidresp), which means that sometimes there are more than one row per child and year. There are five different "Mother & Child" and "Parent" questionnaires in the SOEP and three different "Mother & Child" questionnaires in the SOEP-IS. The information from all eight questionnaires is included the bioage data set. The bioage data set contains all variables with information on the children surveyed in SOEP-IS available within the SOEP-IS and the core SOEP-regardless of whether these variables are also surveyed in the SOEP-IS or only in the core SOEP. The "Mother & Child" and "Parent" questionnaires aim to follow and observe future generations of the SOEP-IS and collect all information in one file, even though the data come from different survey years. As we try to make this process as comprehensive and gap-free as possible, we begin following and documenting the development of children in SOEP-IS households from birth onwards.
Keywords: 330